Kronologi Pewahyuan Al-Qur'an: Rekonstruksi Epistemologis dan Metodologis Asbāb al-Nuzūl dalam Perspektif Klasik dan Kontemporer - Nurfadillah Mustafa; Andi Miswar; Halimah Basri (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
The understanding of asbāb al-nuzūl is now seen not only as an explanatory device for the descent of the verse, but also as a critical instrument for reconstructing the chronological landscape of revelation. In modern development, the issue of the chronology of revelation no longer focuses only on the Makkiyyah–Madaniyyah division, but also includes historical, philological, and socio-political criticism at the time of revelation, as seen in contemporary studies of the last five years. The method of this research is qualitative, based on literature studies that are descriptive-analytical. The results of the study show that asbāb al-nuzūl not only serves as an explanation for the descent of verses, but is also an important instrument in mapping the phases of revelation, identifying the socio-historical context of the verses, and preventing distortions of interpretation. The integration between authentic narration of the companions, the narration of mursal verified through qara'in, criticism of sanad and matan, and modern contextual analysis allows for a more accurate and coherent reconstruction of the chronology of revelation. This study confirms that asbāb al-nuzūl has methodological significance in the development of historical and thematic interpretations, as well as being relevant as a multidisciplinary framework in contemporary Qur'an studies. These findings are expected to contribute to the formulation of a more critical, integrative, and interpretive approach in accordance with the development of modern methodologies.